Fayum, Ägypten: Das Fayum Survey Projekt - Römer, Cornelia (e-Forschungsberichte des DAI, 2023)
The survey covered 10 sites in the north-western Fayum; plans of the sites, most of which were inhabited from the 3rd century BC to the 4th AD, were drawn including all features still visible on the ground. Some of the sites have been massively divested of nearly all their buildings in the beginning of the 20th century, when the ancient building material of mud bricks was used as fertilizer on newly created fields. Today, land reclamation projects encroach on the sites drastically. The survey may be the last chance to record the already scanty remains which nevertheless, and together with the papyrological sources from the same sites, give a lively picture of those villages. The survey was concluded in 2013, and a monograph about the work will appear soon.